2013
DOI: 10.1038/ni.2702
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and transcriptional signatures of stable versus plastic differentiation of proinflammatory γδ T cell subsets

Abstract: Two distinct subsets of γδ T cells that produce interleukin 17 (IL-17) (CD27 − γδ T cells) or interferon-γ (IFN-γ) (CD27 + γδ T cells) develop in the mouse thymus, but the molecular determinants of their functional potential in the periphery remain unknown. Here we conducted a genome-wide characterization of the methylation patterns of histone H3, along with analysis of mRNA encoding transcription factors, to identify the regulatory frames of peripheral IFN-γ-producing or IL-17-producing γδ T cell subsets in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
122
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 60 publications
11
122
0
Order By: Relevance
“…1C). Supporting this result, recent genome-wide epigenetic analysis of CCR6 + IL-17 + gd T cells showed enrichment of active H3K4me2 marks, but no repressive H3K27me3 marks, in the putative RBP-Jk binding site (25.4 kb), suggesting a permissive epigenetic status (31). These results suggest that, in murine gd T cells, ICN1 is specifically bound at the novel promoter site, 25.4 kb upstream of the TSS of IL-7Ra, possibly through the putative RBP-Jk binding site.…”
Section: Icn1 Binding Adjacent To Putative Notch Targets Including Ilsupporting
confidence: 55%
See 1 more Smart Citation
“…1C). Supporting this result, recent genome-wide epigenetic analysis of CCR6 + IL-17 + gd T cells showed enrichment of active H3K4me2 marks, but no repressive H3K27me3 marks, in the putative RBP-Jk binding site (25.4 kb), suggesting a permissive epigenetic status (31). These results suggest that, in murine gd T cells, ICN1 is specifically bound at the novel promoter site, 25.4 kb upstream of the TSS of IL-7Ra, possibly through the putative RBP-Jk binding site.…”
Section: Icn1 Binding Adjacent To Putative Notch Targets Including Ilsupporting
confidence: 55%
“…In an oral infection mouse model with Listeria monocytogenes, IFN-g + IL-17 + gd T cells were detected postinfection (54). A recent genomewide epigenetic analysis revealed that IL-17 + gd T cells had the ability to become IFN-g producers (31). These results suggested the possibility that IFN-g + IL-17 + gd T cells were derived from IL-17 + gd T cells via an unknown mechanism induced by IL-7.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, CD27 (−) γδ T cells in the secondary lymphoid organs have been shown to express higher levels of IL-7R, IL-1R1, and IL-23R than their IFN-γ-secreting counterparts (30,42,43), a property that seems to be transcriptionally acquired and epigenetically sustained (42). Among the type-17-driving cytokines, IL-7 was the most consistently up-regulated throughout ID8 growth, and its exogenous administration showed a tendency to increase the tumor load.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both IL-17 and IFN-γ are likely to be involved in multiple cellular events taking place within the inflammatory tumor microenvironment as well as in draining lymph nodes. Along these lines, it should also be noted that IL-17 + γδ T cells can (under strong inflammatory conditions) differentiate into IL-17/IFN-γ double producers, whose function in the tumor milieu remains to be established (42,57). Gene expression analysis for tgfb, vegfa, cxcl1, mif, il1b, gata6, il17ra, and cd163 was performed by RT-qPCR and normalized to the housekeeping gene hprt.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data from studies of cells in central lymphoid organs suggest that CD27 delineates gd T cell functional subsets, leading to a paradigm shift for how gd T cells are classified (11,29).…”
mentioning
confidence: 99%